Cognitive Behavior Therapy (CBT) in reducing Psychological Impacts on Children Victims of Domestic Violence - Afdal Afdal; Melsi Syawitri; Miftahul Fikri (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2019)
The psychological impact of violence in the household is more severe than the physical impact, including fear, anxiety, fatigue, post traumatic stress disorder, eating and sleeping disorders, and children with severe mental problems can think of suicide. This article aims to present an analysis of the psychological impact on child victims of domestic violence using the literature method and cognitive behavioral therapy approaches that can be carried out by counselors.